(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with different methods of problem solving in preparation for the Olympiads, including teaching based on life experience, concepts, rules and their observations, methods of demonstration based on exercises and examples, their application in describing actions and their properties, textual and plot exercises and examples and in solving them, the formation of thinking skills in students, the use of algebraic and geometric concepts, their interaction with other operations.